An Enlightening Journey - The, Star (The Star, 2018)
Fazalur Rahman who was a Business Management Director of Talentpepz Career Solutions in India. a strong believe in lifelong learning, he found Asia e University (AeU) to be the most ideal institution for him upon through research.